The Effects of Structured School-Based Physical Activity on Fitness and Psychosocial Well-Being in Pre-Adolescents - T, Vivek; T, Parasuraman (Physical Education Theory and Methodology, 2026)
Objectives. The study aimed to identify the impact of structured school-based physical activity program on physical fitness and psychosocial well-being of pre-adolescent students. Materials and Methods. The quasi-experimental pre-test post-test control group research was utilized. Intact schools were used to assign a total of 100 and 120 students (between 10-12 years old), who were to be placed either in Intervention (n = 60) or Control group (n = 60). The intervention course was a 8-week structured physical activity programme carrying out three sessions a week (45 minutes/session), and involved progressive endurance, strength, agility and cooperative activities. The results of the physical fitness were aerobic endurance (PACER), muscular endurance (push-up test), and agility (pro-agility shuttle run). The variables based on psychosocial factors were estimated by self-perception, intrinsic motivation, peer support, and mental well-being through culturally adjusted and validated questionnaires. Data analysis was performed using paired t-tests, mixed ANOVA, and ANCOVA. Effect sizes and confidence intervals were also provided. Results. The intervention group demonstrated statistically significant improvements across all physical fitness and psychosocial outcomes (p < .01), accompanied by large effect sizes (Cohen’s d > 1.60; partial η² > .40). In contrast, the control group showed no statistically significant changes and negligible effect sizes. In addition, strong positive correlations were observed among psychosocial variables, suggesting coordinated improvements across psychological domains. Conclusions. The findings of this study suggest that the structured school-based physical activity significantly enhances the physical fitness and psychosocial well-being of pre-adolescents, thus making it reasonable to incorporate it into the routine school programs.